Compressors and modern process applications - Bloch, Heinz P., 1933- (Wiley-Interscience, 2006)
Gas compressors are used in applications from jet engines to refrigeration, to turbomachinery. Compressors and Modern Process Applications describes the main features of over 300 petrochemical and refining schematics and associated process descriptions that involve compressors and expanders in modern industry.
Keywords: Compressors.; elektronické knihy; electronic books